ENVIRONMENTAL LAW AS AN INSTRUMENT FOR REALIZING SUSTAINABLE TOURISM IN SOUTH LAMPUNG REGENCY - Sholikhul Huda; Achmad Alif Nurbani; Mirza Agung Rahmatullah; Muhammad Habibi (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This article examines the role of environmental law as a key instrument in sustainable tourism development in South Lampung Regency. Tourism significantly contributes to regional economic growth through increased investment, employment opportunities, and community welfare. However, the development of this sector is often accompanied by environmental degradation due to weak ecologically sound management. This research uses normative legal methods with legislative, conceptual, and comparative legal approaches to analyze the role of environmental law as an instrument for realizing sustainable tourism in South Lampung. The research method used in this study is a qualitative approach with a library research method with a normative legal approach. This research is qualitative normative, which emphasizes the analysis of legal norms. Data collection techniques are carried out through documentation analysis by identifying, reviewing, and interpreting legal sources, relevant literature, legal sources used include, Books, Law Number 32 of 2009 concerning environmental protection and management, Law Number 10 of 2009 concerning Tourism, and Government Regulation Number 27 of 2012 concerning Environmental Permits. Then a descriptive-analytical and thematic analysis is carried out, by grouping data into main themes and then drawing conclusions from a general to specific problem, in this case regarding Environmental Law as an Instrument for Realizing Sustainable Tourism in South Lampung. The results of this study indicate that environmental law plays a fundamental role as a controlling instrument in realizing sustainable tourism in South Lampung Regency. Through the implementation of legal instruments such as environmental impact analysis (EIA), environmental permits, the precautionary principle, and the enforcement of legal sanctions, tourism activities can be directed to prevent ecosystem damage.